Volunteer activity and depression among the elderly in China: A study on rural-urban differences. Issue 39 (1st October 2021) - Wang, Yanan; Li, Zhen; Gao, Shang; Fu, Chang
Abstract : Abstract: Participation in volunteer activity has positive effects on health among elderly. Few studies have investigated the association between volunteer activity and depression among Chinese elderly. This study aimed to examine the association between volunteer activity and depression among the elderly in China regarding rural–urban differences. Totally 8255 subjects from the 2015 China Health and Retirement Longitudinal Study were selected in this study. Depression was assessed by 10-item Center for Epidemiologic Studies Depression Scale. Types and frequency of volunteer activity were measured in the questionnaire. Multiple linear regression analysis was used to explore the relationship between volunteer activity and depression of elderly. In our study, the urban elderly had lower depressive scores than rural elderly (6.7 ± 5.8 vs. 9.1 ± 6.7). After adjustment for all covariates, our results revealed that almost daily participation in formal volunteer activities was negatively associated with depression among urban elderly (B = -2.69, SE = 1.05, P  = .010); almost daily caring for a sick or disabled adult was positively associated with depression among both urban and rural elderly (urban:B = 3.13, SE = 1.54, P  = .043; rural:B = 2.56, SE = 1.18, P  = .031). These findings suggested that there was a negative association between formal volunteer activity and depression among urban elderly, while there was a positive association between caring for a sick or disabled adult and depression among both urban and rural elderly. The government should take effective measures to encourage the elderly to participate in formal volunteer activities to prevent them from depression.